Sequence Requirements for the Assembly of Simian Virus 40 T Antigen and the T-Antigen Origin Binding Domain on the Viral Core Origin of Replication - Kim, Henry Y. (American Society for Microbiology, 1999)
The regions of the simian virus 40 (SV40) core origin that are required for stable assembly of virally encoded T antigen (T-ag) and the T-ag origin binding domain (T-ag-obd(131–260)) have been determined. Binding of the purified T-ag-obd(131–260) is mediated by interactions with the central region of the core origin, site II. In contrast, T-ag binding and hexamer assembly requires a larger region of the core origin that includes both site II and an additional fragment of DNA that may be positioned on either side of site II. These studies indicate that in the context of T-ag, the origin binding domain can engage the pentanucleotides in site II only if a second region of T-ag interacts with one of the flanking sequences. The requirements for T-ag double-hexamer assembly are complex; the nucleotide cofactor present in the reaction modulates the sequence requirements for oligomerization. Nevertheless, these experiments provide additional evidence that only a subset of the SV40 core origin is required for assembly of T-ag double hexamers.